What is the effect of Moringa oleifera on the ruminal dynamics? A systematic review - Garcia Quintero, Indira Isis (2017)
Moringa oleifera is a tree with high potential to meet nutritional deficiencies in tropical production systems, especially in ruminants due to its nutritional value, palatability, biomass production and adaptability to harsh conditions. This systematic review aimed to highlight the effect of fodder consumption in the ruminal dynamics. A search protocol was implemented to systematize the process for tracking the information. The search identified studies related to the effect of consumption of M. oleifera on rumen dynamics in terms of digestibility and degradability of dry matter, production of gases and changes in microbial population. Seventeen bibliographic databases were searched yielding 28 articles and 15 rated as acceptable quality for the purpose of this study. It was concluded that there was a high variability in the results published which is related to the diversity of conditions in the studies, material used and mixtures with other forages and concentrates, as well as the methodologies and techniques used.